The role of information quality processing in determining purchase intentions through social psychological distance - I Made Bayu Dirgantara; Habib Maulana Akbar (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2022)
The expansion of e-commerce users in Indonesia parallels the growing internet penetration. However, this does not necessarily positively affect e-commerce service providers, as there are other obstacles, including a healthy environment. Because the quality of the information in e-commerce is maintained, a healthy ecosystem develops. Consequently, this study will delve deeper into the significance of information quality in e-commerce services. Data gathered from 143 respondents and analyzed using Structural Equation Modeling (SEM) reveal that the quality of information has a positive and statistically significant effect on purchase intention via social psychological distance and trust.